Building brand commitment from internal brand management and employee-based brand equity factors - Sebopa, Caroline Boitumelo (My University, 2021)
Famous Brands is a JSE listed company with a market capitalisation of over R10 billion and is the largest food services franchisor in Africa, boasting of over 24 brands. The organisation has over 2800 restaurants in Africa, the Middle East and the United Kingdom. Some of their market-leading brands include Steers, Debonairs Pizza, Wimpy, Mugg n Bean, Fishaways, GBK, and Turn n Tender, amongst others. Various success factors of the organisation have been documented and these have included acquisitions, joint ventures, and vertical integration. The success of Famous Brands could also have been generated from its brand knowledge structure held by customers and employees. The brand knowledge, role clarity and brand commitment that employees hold of their company’s brand have been found to be important dimensions necessary for building employee-based brand equity (EBBE). When EBBE is built, it is reported that organisations or brand owners benefit in various ways, such as employees’ motivation, retention, satisfaction, brand citizenship behaviour, willingness to endorse the brand, and most importantly, it can lead to increased brand commitment. Brand commitment can be seen through the attachments an employee has with a brand and the extent to which they are willing to go the extra mile to help an organisation reach its objectives. These benefits can be achieved if there is good internal brand management. Despite the benefits of EBBE, and because there is the notion that the strength of the brand lies in what customers know and feel about the brand, marketing practitioners and academics have focused too much on how customer-based brand equity (CBBE) is built, measured and managed. The building and measuring of the contribution of EBBE has received limited attention, even though the resource-based view theory posits that superior customer value is created when the importance of all resources (i.e., brands and employees) are recognised and nurtured for competitive advantage. Employees are important company resources, and for them to build good brand citizenship behaviours, the social exchange theory suggests that they have to perceive an organisation to be caring and supportive, and the social identity theory suggests that employees need to identify with the organisation. iv In one of the first empirically tested model on how EBBE can be built and measured, King and Grace (2010) showed that the benefits of EBBE can be achieved if a brand is internally well managed through openness, good human factors, information generation from studying employee needs, management support, brand knowledge dissemination, which then leads to role clarity and brand commitment. These factors impacted on the EBBE benefits: brand citizenship behaviour, employee satisfaction, brand allegiance, and employee willingness to endorse the organisation. Subsequent studies have tested King and Grace’s (2010) model in various service industries. However, the importance of testing the resource-based view theory in different industry contexts has been recommended. Also, the internal brand management factors may first impact on employee satisfaction, before leading to EBBE benefits and brand commitment. Considering the success of Famous Brands in South Africa and the fact that few studies have tested the sources and outcomes of EBBE in the food service industry, this study integrated King and Grace’s (2009; 2010) EBBE model and Du Preez and Bendixen’s (2015) internal brand management (IBM) model to examine the extent to which IBM and employee satisfaction impact overall EBBE, and whether the overall EBBE drives employee brand commitment. An integrated conceptual model with twelve hypotheses was developed. To test the hypotheses, data was collected from 404 Famous Brands employees in South Africa through self-administered questionnaires. Structural equation modelling was used to test the hypotheses. Of the twelve hypotheses that were tested, ten were supported and two were not. Internal brand communication, role clarity, management support and rewards had a positive impact on employee satisfaction. Employee satisfaction positively impacted brand citizenship behaviour, brand endorsement and brand allegiance. Employees who displayed brand citizenship behaviours, endorsed the brand/organisation and intending to continue working for the organisation were found to be committed to the organisation. Internal marketing research and employee satisfaction were found to have a negative relationship, as well as employee satisfaction and brand commitment. This study contributes to theory on IBM, employee satisfaction, EBBE and employee brand commitment, particularly in the food service industry in South Africa. These findings can help better understand employees and how their commitment to a company’s brand can be gained. The study can help managers and marketers to understand the factors leading to the commitment of the employees of Africa’s biggest food services franchisor and the learnings can be used in their own organisations. This study’s findings can also be used to develop IBM programmes for organisations.
A thesis submitted to the in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, School of Economics and Business Sciences, University of the Witwatersrand, Johannesburg, 2021